School heterotopia and El Sembrador. Reflections on other educations (Praxis Educativa, 2025)
This article deals with an educational experience in southeastern Mexico as a bid to reformulate the  purposes of public school towards a horizon of freedom. The educational practices and the organization of the   school function based on the praxis of a bilingual teacher, El Sembrador, allows us to approach the heterotopic irruption that shows how the alternative school offers a different space for the construction of  knowledge, where other teaching-learning processes flourish, breaking the dominant norm of what it means to do school and transgressing the formal curriculum. As an essay based on a documentary, this article describes the conditions where bifurcations of formal education are built and how the practices of El Sembrador, as an educator committed to the common good, performs situated actions that shed clues on the transformation of the school into a space for the reproduction of happiness in the students.
Keywords: rural education; school; heterotopia; alternative pedagogies; teaching